Dimensions, Measures, and Contexts in Psychological Investigations of Curiosity: A Scoping Review - Yong Jie Yow; Jonathan E. Ramsay; Patrick K. F. Lin; Nigel V. Marsh (Behavioral Sciences, 2022)
The study of curiosity as a construct has led to many conceptualisations, comprising of different dimensions. Due to this, various scales of curiosity have also been developed. Moreover, some researchers have conceived of curiosity as a general trait-like, while others have included contexts, such as the workplace, or education when investigating curiosity. This scoping review aims to scope the extant psychological literature on curiosity in order to better understand how it has been studied, specifically with regard to its dimensions, measures, and contexts. A total of 1194 records were identified, with 245 articles meeting the inclusion criteria. Results suggest that the majority of curiosity research examined curiosity as having multiple dimensions and analysed the dimensions individually, with a deprivation-type curiosity playing the biggest role. The measure most commonly used was the Epistemic Curiosity Scale, which also consisted of a deprivation-type curiosity as one of the dimensions. Findings also implied that curiosity was most studied in the context of the workplace. Supplementary findings included a lack of representation of non-Western countries, as well as needing to cross-validate a recently developed curiosity scale. This scoping review represents a consolidation of the curiosity literature and how it can further prosper.